Size Board of Commissioners, Independent Commissioners and Audit Committee on Audit Report Lag - Anwar, Rapika; Suleman, Nurjana; Thalib, Maryati Kadir (Golden Ratio of Auditing Research, 2022)
This study examines whether the size of the board of commissioners, independent commissioners, and audit committees affects audit report lag in manufacturing companies listed on the IDX. The sampling process uses the purposive sampling method; this method is used so that the samples taken are under the criteria—sources of data in the study obtained from companies in the form of secondary data. And the data processing method used is multiple regression analysis, with the help of SPSS for Windows software. The results of this study indicate that partially the variable size of the board of commissioners has a positive and significant effect on audit report lag. In contrast, the variables of independent commissioners and audit committees have a negative and significant impact on audit report lag. The results of this study can also be used as input and a reference for companies in observing the implementation of the preparation of quality company financial reports to reduce audit report lag.